Struggling Against Social Exclusion: A Qualitative Study on the Odia Language Speakers in the Tea Community - Tanti, Pollob Kumar; Haider, Mohammad Mojur Ul (Mother Language, 2025)
The tea community people of Bangladesh have their own languages. Odia is one of them, The Bangladesh government is currently implementing initiatives to protect the language and culture of indigenous communities. Primary education in the mother tongue will help these ethnic communities protect their rights, and it is a process of inclusion. But the tea community is deprived of this initiative. The government does not provide them with any opportunities to get primary education in their mother tongue. It is a process of social exclusion. A total of 40 interviews had been carried out with the participants following purposive sampling to conduct this research. Observation, 24 in-depth interviews (IDI), 12 key informant interviews (KII), 1 Focus Group Discussion (FGD) methods were followed to conduct the research. Results revealed that, the Odia language is a rich language having a written form, an alphabet, and an extensive amount of literature. Despite its richness, the Odia language of the tea community is being ignored day by day. As a result, the new generation is losing interest in communicating in their mother tongue. As these things are in the opposite position of inclusion, they can be identified as excluded. Mother Language, 2024; 8(1-2): 153-173